Leasing impact on transformation processes in the Russian agricultural sector under sanctions pressure - A. A. Kiritsa; Yu. V. Chutcheva (Вестник университета)
At   the present stage, the issues of   sustainable development of  the Russian agricultural sector and strengthening its technical potential in  the context of   sanctions pressure are becoming especially relevant. One of   the most useful tools in   solving these problems is  leasing. The purpose of   this article is  to analyse promising directions for the development of   leasing as   the effective form of   technical support for agricultural production in  the current conditions. The study has used general scientific methods (analysis and synthesis, economic and statistical, graphical, etc.). The main trends now emerging in   the domestic market are highlighted from the point of  view of  manufacturers of   agricultural machinery and goods. With consideration to  the current situation in   the domestic market, decreased prices for agricultural products and rapid growth of   prices for agricultural machinery, the most promising areas for the use of  leasing mechanisms have been proposed to   help accelerate technical re-equipment in   the agricultural sector: application of   leasing solutions in   the agricultural industry that have already been tested and proven successful in   other market segments (for example, subscription, agrocarsharing, etc.); combination of   leasing mechanisms with trade-in programmes which make it  possible to  comprehensively solve issues not only of   updating machinery and tractor fleet, but also of  recycling worn-out agricultural equipment; use of   leasing mechanisms for the development of  machine and technological complexes as a   modern form of  joint use of   machinery in  agriculture which allows accelerating technical equipment of   the industry. The proposed directions can help ensure systemic development and quicken the technical re-equipment of   the Russian agricultural sector.